Putrescine mitigates NaCl-induced stress by modulating gene expression, antioxidants, and ethylene level in tomato - Yalaga Rama Rao; Priya Yadav; Varsha Rani; Devayani Muley; Ranjan Kumar Sahoo; Brajendra; Shashi Bhushan Kumar; Ritu Gill; Sarvajeet Singh Gill; Mohammad Wahid Ansari; Narendra Tuteja (Plant Signaling & Behavior)
Plant development and productivity are significantly hindered by salt stress, leading to substantial financial losses in the agriculture sector. Salinity stress negatively impacts the overall growth, physiology, and metabolism of plants. Specifically, NaCl stress is particularly harmful to tomato plants, causing suppression of seedling growth, accumulation of sodium (Na+) and chloride (Cl−) ions, disrupted ion homeostasis, reduced proline and chlorophyll content, and impairment of antioxidant enzyme systems. This research aimed to investigate the role of exogenous putrescine (PUT) application on tomato (Solanum lycopersicum L.) seedlings under NaCl stress (250 mm) to determine its potential protective effects. Various physio-biochemical attributes were estimated using precise protocols for NaCl-treated, PUT-treated, and untreated controlled tomato seedlings also analyzed for the expression of ACS1, NHX1, HKT1;2, and SOS1 genes. Additionally, ACC synthase activity, ethylene content, electrolyte leakage, proline content, Na+ and potassium (K+) ion content, lycopene content, and antioxidant enzyme activities were examined. Results indicated that PUT application enhanced the expression of ACS1, NHX1, HKT1;2, and SOS1 genes increase the ACC synthase activity, ethylene content, proline content, and Na+ and K+ ion content, while reducing electrolyte leakage. Furthermore, PUT application significantly increased the activity of superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), and glutathione reductase (GR), as well as other morphological parameters. Overall, our research demonstrated the potential benefits of PUT applications for enhancing crop growth and improving salt stress tolerance, which are crucial for agronomy.